Composite sodium-ion positive electrode material and preparation method thereof

Prussian blue nanocubes were synthesized and surface-modified by co-precipitation, and then hydrothermally coated with a polyanion shell to form a composite sodium-ion cathode material. This solved the structural instability problem of Prussian blue during charge and discharge, and improved the cycle performance and energy density of the battery.

CN122267133APending Publication Date: 2026-06-23WUXI ZHAONA NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610374795.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-25
Publication Date
2026-06-23

AI Technical Summary

Technical Problem

Prussian blue, the cathode material for sodium-ion batteries, undergoes lattice structure changes and side reactions triggered by water of crystallization during charging and discharging, leading to unstable electrochemical performance. In addition, lithium-ion batteries, which are scarce in resources, are facing a shortage problem.

Method used

Uniform Prussian blue nanocubes were synthesized by coprecipitation and amino functional groups were introduced through surface modification. Subsequently, a polyanionic shell was hydrothermally coated to form a composite structure with "Prussian blue as the core and polyanionic shell" to enhance the stability and cycling performance of the material.

Benefits of technology

It improves the cycle stability and energy density of sodium-ion batteries, reduces structural damage, and extends cycle life. It utilizes the stable structure of polyanionic materials to provide physical barriers and interfacial stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122267133A_ABST
    Figure CN122267133A_ABST
Patent Text Reader

Abstract

The application discloses a composite sodium-ion positive electrode material and a preparation method thereof; in the preparation, iron-based Prussian blue FeHCF is prepared through co-precipitation, and then a polyanion shell is coated through hydrothermal reaction; the inner core of the prepared Prussian blue is surface-modified, the surface modification comprises the following steps: using a positively charged polymer to make the surface of the Prussian blue positively charged through electrostatic adsorption, or using a coupling agent to introduce functional groups such as amino groups, so that the adsorption capacity of the surface of the Prussian blue to polyanion precursor ions is enhanced, and the growth of a uniform and dense shell is promoted. In the composite structure positive electrode material with the core of Prussian blue and the shell of polyanion provided by the application, the inner core Prussian blue plays a role in high capacity and excellent rate performance; the outer shell polyanion mainly plays a role in physical barrier and stable interface, the stable structure and excellent cycle performance of the polyanion material are used to provide a solid 'protective shell' for the whole particle, reduce the structural damage in the cycle process, and improve the overall cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium / sodium-ion battery technology, and relates to a composite sodium-ion cathode material and its preparation method. Background Technology

[0002] In recent years, lithium-ion batteries (LIBs) have developed rapidly and are widely used, becoming one of the most important energy storage technologies. With the development of electric vehicles and large-scale new energy sources, the demand for rechargeable batteries is increasing daily. However, the small total reserves of lithium resources, their uneven global distribution, and poor availability make lithium resources very expensive. Limited lithium resources will inevitably face shortages; at the current rate of consumption, without considering recycling, they are expected to be depleted in over sixty years. Implementing LIBs for large-scale energy storage in the face of huge market demand is not a wise choice. On the other hand, the unsatisfactory cycle stability and low energy density of lead-acid batteries restrict their further development in more application scenarios. Developing new energy storage battery systems that are abundant in resources, inexpensive, have high specific capacity, high power, long cycle life, and are environmentally friendly, in line with energy development principles, is urgently needed. SIBs, due to their similar electrochemical properties to LIBs and abundant resource reserves, are expected to become the mainstream direction for future rechargeable battery development. Sodium-ion batteries, with their advantages of abundant resources and low cost, have shown broad application potential in many fields, such as large-scale energy storage systems, low-speed electric vehicles, and the construction of 5G communication base stations.

[0003] Due to the large volume and weight of sodium ions, sodium-ion batteries typically exhibit lower capacity and poorer cycle stability compared to lithium-ion batteries. Prussian blue and its analogues, with their unique three-dimensional framework structure and large porosity, are among the most important cathode materials for sodium-ion batteries; however, some problems remain in practical applications. For example, changes in the microstructure of the crystal lattice during charging and discharging, as well as the large number of vacancies and water of crystallization within the structure, lead to significant differences between their electrochemical performance and expectations. Summary of the Invention

[0004] To address the shortcomings of the existing technology, the present invention aims to provide a composite sodium-ion cathode material and its preparation method. The main steps of this preparation method include: 1) synthesis and pretreatment of the Prussian blue core; 2) hydrothermal coating of the polyanion shell. Specifically, in the synthesis and pretreatment of the Prussian blue core, uniformly sized Prussian blue nanocubes are synthesized using a co-precipitation method. The reaction concentration, temperature, and dropping rate are strictly controlled to obtain monodisperse particles.

[0005] Key steps: Preparation of Prussian blue and surface modification of the synthesized Prussian blue. Functional groups such as amino groups are introduced by using coupling agents (3-aminopropyl)triethoxysilane (APTES), poly(diallyldimethylammonium chloride) (PDDA), and polyethyleneimine (PEI); and the amino functional groups strengthen the binding with the polyanion material through electrostatic attraction, coordination, and hydrogen bonding with the polyanion material. Therefore, surface modification of the synthesized Prussian blue can enhance the adsorption ability of the Prussian blue surface to polyanion precursor ions and promote the growth of a uniform and dense shell layer.

[0006] Specifically, the above object of the present invention is achieved by the following technical solutions:

[0007] <First aspect> The present invention provides a composite sodium ion cathode material, wherein the cathode material has a Prussian blue core and a carbon-coated polyanion cathode material shell.

[0008] As an embodiment, the chemical formula of the Prussian blue is Na x Fe[Fe(CN)6] y ·nH2O, x ≤ 1, 0 < y < 1, and n is the water content of crystal water; the chemical formula of the polyanion is Na4Fe3(PO4)2P2O7.

[0009] As an embodiment, when preparing the cathode material, a Prussian blue core is prepared by co-precipitation, and the obtained core is Prussian blue with surface modification; the surface modification includes making the Prussian blue surface positively charged by electrostatic adsorption using a positively charged polymer or introducing an amino functional group using a coupling agent.

[0010] <Second aspect> The present invention provides a preparation method of a composite sodium ion cathode material, and the method includes the following steps: S1. Co-precipitation to prepare iron-based Prussian blue FeHCF: S1-1. An iron source, sodium ferrocyanide, and a chelating agent are dissolved in deionized water to form solution A; S1-2. A positively charged polymer or a coupling agent is dissolved in deionized water to form solution B; S1-3: Under the condition of introducing N2 and a constant oil bath at 40 - 55 °C, solution A is added to solution B and reacted until crystallization is sufficient; heating is stopped and aged for a period of time; centrifuged, washed, and the precipitate is collected and vacuum dried to obtain FeHCF; S2. Hydrothermal coating of the polyanion shell: S2-1. FeHCF particles are dispersed in deionized water to form solution C; S2-2. A powdery iron source and an additive are stirred in deionized water to obtain solution D; S2-3. Add solution D to solution C, let it stand at room temperature for a period of time, and then heat and stir to form Fe@FeHCF solution; S2-4. Add phosphorus source, carbon source and sodium source to Fe@FeHCF solution, stir until completely dissolved to allow the reaction to occur, and pyrophosphate ions are deposited on the Fe@FeHCF surface; dry; S2-5. The composite sodium ion cathode material is obtained by heat treatment at 500℃-600℃ under circulating high-purity nitrogen gas and then cooled.

[0011] As one implementation scheme, in step S1-1, the iron source is at least one of FeSO4·7H2O and Fe(NO3)3.

[0012] As one embodiment, the chelating agent is one of trisodium citrate (Na3C6H5O7·2H2O), disodium ethylenediaminetetraacetate (Na2EDTA), and sodium oxalate.

[0013] As one implementation scheme, in step S1-1, the molar ratio of iron source, sodium ferrocyanide, chelating agent and solvent water is 1:(1~1.5):1:(100~400).

[0014] As one implementation, in steps S1-2, the positively charged polymer is at least one of polydiallyldimethylammonium chloride (PDDA) and polyvinylpyrrolidone (PVP).

[0015] As one embodiment, the coupling agent is one of (3-aminopropyl)triethoxysilane (APTES) and polyethyleneimine (PEI). If an aluminate coupling agent is used, it cannot enhance the adsorption capacity of the Prussian blue surface for polyanionic precursor ions and promote the growth of a uniform and dense shell because it cannot introduce amino groups.

[0016] As one embodiment, the mass ratio of the positively charged polymer or coupling agent to the iron source and water is 1:(1-2):(100-800).

[0017] In one implementation, in steps S1-3, solution A is added dropwise to solution B at a rate of 0.1–0.3 ml / min. The aging time is 24–36 h. The vacuum drying is performed at 100 °C for 24–36 h. In some implementation examples, in step S1-3, solution B is placed in a constant 50 °C oil bath under N2 purging, and solution A is slowly added dropwise to solution B in the oil bath at a rate of 0.1–0.3 ml / min. After titration, the solution is rotated for 7 h at a constant temperature and rotation speed (500 rpm) to ensure sufficient crystallization. Finally, the temperature is turned off and the solution is aged for 24–36 h. After the reaction, the precipitate is collected by centrifugation and subjected to multiple centrifugations and washings with ethanol; then further centrifugation and washing with anhydrous ethanol are performed to ensure that excess ions in the material are removed; then the sample is placed in a vacuum drying oven and vacuum dried at 100 °C for 24–36 h to obtain an iron-based Prussian blue analog named FeHCF.

[0018] As one implementation scheme, in step S2-2, the particle size of the powdered iron source is 1 to 1.2 micrometers (D50), and the iron source is one of iron phosphate and ferric oxide.

[0019] As one embodiment, the additive is one or more of polyethylene glycol, polyvinyl alcohol, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate. The additive serves to achieve uniform dispersion.

[0020] As one implementation, in steps S2-4, the phosphorus source is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0021] As one embodiment, the sodium source is one or more of sodium acetate, sodium carbonate, sodium bicarbonate, sodium hydrogen phosphate, sodium dihydrogen phosphate, sodium oxalate, sodium chloride, sodium nitrate, and sodium citrate.

[0022] As one embodiment, the carbon source is a reducing acidic organic carbon source, including one or more of citric acid, sucrose, oxalic acid, maltose, fructose, and glucose.

[0023] As one implementation scheme, in S2-2, the mass ratio of the powdered iron source, additive and deionized water is (1-10):(2-5):(50-100).

[0024] In one implementation scheme, in S2-3, the mass ratio of FeHCF particles to powdered iron source is 8 to 12:1.

[0025] As one implementation scheme, in S2-4, the molar ratio of the phosphorus source, carbon source, sodium source and powdered iron source is (0.8~1.0):(34~38):(1.5~3):3.

[0026] As one implementation, the drying process involves drying at 65-75°C for 20-30 hours.

[0027] In one implementation scheme, S2-5, the temperature is increased to 500℃-600℃ at a rate of 2-4℃ / min under flowing high-purity nitrogen and held for 8-12 hours. In some implementation examples, the obtained dry powder is placed in a tube furnace and heated to 500℃-600℃ at a rate of 3℃ / min under flowing high-purity nitrogen and held for 10 hours. After cooling, a uniformly carbon-coated Na2FeP2O7 / C@FeHCF composite material is obtained.

[0028] <Third aspect> The present invention provides a sodium-ion battery, wherein the active material contained in the positive electrode of the sodium-ion battery is the aforementioned composite sodium-ion positive electrode material, or the composite sodium-ion positive electrode material prepared by the aforementioned method.

[0029] As one embodiment, the positive electrode slurry is obtained by mixing 85-95 wt% of composite sodium-ion positive electrode material, 1-3 wt% of conductive agent acetylene black, 2-5 wt% of binder PVDF and dispersant carbonic acid, wherein the mass ratio of carbonic acid to composite sodium-ion positive electrode material is 0.6-1:100.

[0030] Compared with the prior art, the present invention has the following beneficial effects: 1) This invention designs a composite cathode material with "Prussian blue as the core and polyanion as the shell". The Prussian blue core plays a role in providing energy by leveraging its high capacity and excellent rate performance. The polyanion shell mainly plays the following roles: a) Physical barrier: protecting the Prussian blue core and preventing it from directly contacting the electrolyte, thereby inhibiting side reactions caused by water of crystallization; b) Stable interface: utilizing the stable structure and excellent cycling performance of the polyanion material, it provides a robust "protective shell" for the entire particle, reducing structural damage during cycling and improving the overall cycle life.

[0031] 2) This invention provides a method for preparing a composite cathode material with a "Prussian blue core and polyanion shell," wherein, a. Synthesis and Pretreatment of Prussian Blue Cores: Uniform Prussian blue nanocubes were synthesized using a co-precipitation method. Strict control of reaction concentration, temperature, and dropping rate was maintained to obtain monodisperse particles. Preparation of Prussian Blue and Surface Modification of the Synthesized Prussian Blue: Positively charged polymers (such as polydiallyldimethylammonium chloride PDDA and polyvinylpyrrolidone PVP) can be used to electrostatically adsorb onto the surface, or silane coupling agents (such as APTES) can be used to introduce functional groups such as amino groups. This enhances the adsorption capacity of the Prussian blue surface for polyanionic precursor ions, promoting the growth of a uniform and dense shell.

[0032] b. Hydrothermal coating of polyanionic shell: uniform coating, simple process and easy to control. Attached Figure Description

[0033] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 The flowchart shows the preparation process of Na2FeP2O7 / C@FeHCF composite material; Figure 2 The coin cell capacity-voltage curve for Example 1; Figure 3 The curves show the cycle retention rates of Examples 1 and 2 and Comparative Example 1. Detailed Implementation

[0034] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0035] Example 1 This embodiment relates to the Na2FeP2O7 / C@FeHCF composite material and its preparation. The preparation process is as follows: Figure 1 As shown. Specifically includes: 1. Synthesis of Prussian blue cathode material by co-precipitation method (1) Prussian blue cathode material was synthesized by co-precipitation method and FeHCF was synthesized by appropriate optimization. 0.2M FeSO4·7H2O, 0.3M sodium ferrocyanide and 0.2M Na3C6H5O7·2H2O were dissolved in 200ml of ultrapure water by magnetic stirring to form solution A.

[0036] (2) Dissolve 6g of APTES (3-aminopropyltriethoxysilane) in 500ml of ultrapure water by magnetic stirring to form solution B.

[0037] (3) Place solution B in a constant oil bath at 50°C. Under the condition of passing N2, slowly add solution A to solution B in the oil bath at a rate of 0.2 ml / min. After titration, rotate for 7 hours under the condition of constant temperature and rotation speed to ensure that the material is fully crystallized. Finally, turn off the temperature and age for 24 hours.

[0038] (4) After the reaction is complete, the precipitate is collected by centrifugation and then subjected to multiple centrifugations and washing with ethanol. Then, anhydrous ethanol is used for further centrifugation and washing to ensure that excess ions in the material are cleaned. The sample is then placed in a vacuum drying oven and vacuum dried at 100°C for 24 hours to obtain the surface-modified iron-based Prussian blue analogue named FeHCF. 2. Hydrothermal coating of polyanion shell: (5) Disperse FeHCF particles in 50 mL of deionized water to form solution C.

[0039] (6) Mix 4.34 g of commercially available ferric phosphate with D50=1 μm and 1.2 g of polyethylene glycol in 50 mL of deionized water to obtain solution D.

[0040] (7) Slowly add solution D to solution C (mFeHCF:mFe phosphate = 10:1), let it stand at room temperature for a period of time (30 min), and then heat and stir the above mixed solution to form solution E (Fe@FeHCF solution).

[0041] (8) Weigh 1.20g of diammonium hydrogen phosphate, 65g of glucose and 2.32g of sodium carbonate, add them to solution E and stir until completely dissolved to allow the reaction to occur, so that pyrophosphate ions are uniformly deposited on the Fe@FeHCF surface.

[0042] (9) After stirring, place the material in a 70℃ oven to dry for 24 hours.

[0043] (10) The obtained dry powder was placed in a tube furnace and heated to 600℃ at a rate of 3℃ / min under flowing high-purity nitrogen for 10h. After cooling, a uniformly carbon-coated Na2FeP2O7 / C@FeHCF composite material was obtained. Electron micrographs show that the shell polyanion was successfully deposited or grown on the surface of the material with Prussian blue cathode material as the core.

[0044] 3. Cell fabrication: (11) Mix 95wt% of sodium-containing cathode material Na2FeP2O7 / C@FeHCF, 2wt% of conductive agent acetylene black, 3wt% of binder PVDF and dispersant carbonic acid, with a mass ratio of carbonic acid to Na2FeP2O7 / C@FeHCF of 0.8:100. Stir at 1200 r / min for 20 min using a low-speed stirrer. Then add a certain amount of solvent NMP (N-methylpyrrolidone), where NMP:NFPP = 1:1 (mass ratio). Stir at 2400 r / min for 60 min using a low-speed stirrer. Then uniformly coat the prepared cathode slurry onto an aluminum foil (cathode current collector) with a thickness of 14 μm and an areal density of 10 mg / cm³. 2 After drying (baking), rolling, slitting, and die-cutting, the positive electrode sheet is prepared. The electrode sheet is then baked at 150℃ for 10 hours. The maximum compacted density of the positive electrode sheet is determined by the degree of opacity after being folded twice during rolling; this density is 2.3 g / cm³. 3 .

[0045] (12) Preparation of negative electrode sheet: 93.6 wt% of hard carbon negative electrode material, 1.2 wt% of CMC binder solution, and 2 wt% of acetylene black conductive agent were mixed and stirred at 1200 r / min for 20 min using a low-speed mixer. The CMC binder solution was prepared from deionized water and CMC (carboxymethyl cellulose), with a CMC content of 1.2 wt%. Then, 40% solid content styrene-butadiene rubber latex binder was added at an amount of 3.2 wt%, and the mixture was stirred at 300 r / min for 1 hour. The prepared negative electrode slurry was then uniformly rolled onto an aluminum foil (negative electrode current collector) with a thickness of 14 μm and an areal density of 6.3 mg / cm³. 2 After drying (baking), slitting, and die-cutting, the negative electrode sheet is prepared.

[0046] (13) The obtained positive electrode, negative electrode and 16μm thick polypropylene separator are stacked in sequence in the order of separator / negative electrode / separator / positive electrode. The number of positive electrode is 15 and the number of negative electrode is 16. The obtained sodium ion electrode core is sealed in aluminum-plastic film to obtain sodium ion battery with a designed capacity of 2Ah.

[0047] (14) The electrolyte is composed of sodium hexafluorophosphate and solvent. The concentration of sodium hexafluorophosphate is 1 mol / L. The solvent is ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC) = 1:1:1 (mass ratio). The obtained sodium-ion battery is baked in a high-temperature vacuum chamber for 24 hours. The electrolyte is injected at a rate of 5 g / cell. After the electrolyte is injected, the sodium-ion battery is prepared by processes such as formation, aging, and capacity testing. The battery is degassed after formation and before aging.

[0048] Example 2 This embodiment relates to the Na2FeP2O7 / C@FeHCF composite material and its preparation. The preparation process is as follows: Figure 1 As shown. Specifically includes: 1. Synthesis of Prussian blue cathode material by co-precipitation method (1) Prussian blue cathode material was synthesized by coprecipitation method and FeHCF was synthesized by appropriate optimization. 0.2M FeSO4·7H2O, 0.3M sodium ferrocyanide and 0.2M Na3C6H5O7·2H2O were dissolved in 200ml of ultrapure water by magnetic stirring to form solution A.

[0049] (2) Dissolve 6g of PDDA (polydiallyl dimethyl ammonium chloride) in 500ml of ultrapure water by magnetic stirring to form solution B.

[0050] (3) Place solution B in a constant oil bath at 50°C. Under the condition of passing N2, slowly add solution A to solution B in the oil bath at a rate of 0.2 ml / min. After titration, rotate for 7 hours under the condition of constant temperature and rotation speed to ensure that the material is fully crystallized. Finally, turn off the temperature and age for 24 hours.

[0051] (4) After the reaction is complete, the precipitate is collected by centrifugation and then subjected to multiple centrifugations and washing with ethanol. Then, anhydrous ethanol is used for further centrifugation and washing to ensure that excess ions in the material are cleaned. The sample is then placed in a vacuum drying oven and vacuum dried at 100°C for 24 hours to obtain the surface-modified iron-based Prussian blue analogue named FeHCF. 2. Hydrothermal coating of polyanion shell: (5) Disperse FeHCF particles in 50 mL of deionized water to form solution C.

[0052] (6) 4.34 g of commercially available ferric phosphate with D50=1 μm and 1.2 g of polyethylene glycol were stirred evenly in 50 mL of deionized water to obtain solution D.

[0053] (7) Slowly add solution D to solution C (mFeHCF:mFe phosphate = 10:1), let it stand at room temperature for a period of time (30 min), and then heat and stir the above mixed solution to form solution E (Fe@FeHCF solution).

[0054] (8) Weigh 1.20g of diammonium hydrogen phosphate, 65g of glucose and 2.32g of sodium carbonate, add them to solution E and stir until completely dissolved to allow the reaction to occur, so that pyrophosphate ions are uniformly deposited on the Fe@FeHCF surface.

[0055] (9) After stirring, place the material in a 70℃ oven to dry for 24 hours.

[0056] (10) The obtained dry powder was placed in a tube furnace and heated to 600°C at 3°C / min under flowing high-purity nitrogen for 10 hours. After cooling, a uniformly carbon-coated Na2FeP2O7 / C@FeHCF composite material was obtained.

[0057] Example 3: In the co-precipitation method for synthesizing Prussian blue cathode material, step (2) uses PEI (polyetherimide), and the rest is the same as in Example 1.

[0058] Example 4: The temperature in step (10) of the hydrothermal coating of the polyanionic shell is increased to 500°C, and the rest is the same as in Example 1.

[0059] Example 5: The temperature in step (10) of the hydrothermal coating of the polyanionic shell is increased to 550°C, and the rest is the same as in Example 1.

[0060] Comparative Example 1: The difference from Example 1 is that pure in-situ carbon-coated commercial Prussian blue cathode material was used as the cathode material for the battery cell. That is: (5) Disperse FeHCF particles in deionized water to form solution C.

[0061] (6) Weigh 65g of glucose and add it to solution C and stir until completely dissolved.

[0062] (7) After stirring and evaporation, place the material in a 70°C oven to dry for 24 hours.

[0063] (8) The obtained dry powder is placed in a tube furnace and heated to 600°C at 3°C / min under flowing high-purity nitrogen for 10 hours. After cooling, a uniformly carbon-coated C@FeHCF composite material is obtained.

[0064] Comparative Example 2: The difference from Example 1 is that pure sodium iron phosphate pyrophosphate is used as the positive electrode material of the battery cell.

[0065] Comparative Example 3: The difference from Example 1 is that: 1. The Prussian blue cathode material synthesized by coprecipitation method is Prussian blue cathode material without the addition of coupling agent as the core of the cathode material, and the preparation method of polyanionic cathode material is the same as that in Example 1.

[0066] The electrochemical performance of the sodium-ion batteries prepared in Examples 1-5 and Comparative Examples 1-3 is shown in Table 1 below. Specific capacity was tested using a coin cell test, with the positive electrode being the experimental electrode and the negative electrode being a sodium sheet. The cells were charged at 0.1C to 4.2V and discharged at 0.1C to 1.5V. The electrodes were then used to fabricate 2Ah cells for energy density and 1C / 1C cycle testing, with a cycle voltage range of 4.2~1.5V.

[0067] Preparation of the positive electrode sheet: 95 wt% of the positive electrode material, 2 wt% of the conductive agent acetylene black, and 3 wt% of the binder PVDF were mixed and stirred at 1200 r / min for 20 min using a low-speed stirrer. Then, a certain amount of solvent NMP was added, wherein the ratio of NMP to sodium iron phosphate pyrophosphate positive electrode material was 1:1 (mass ratio). The mixture was stirred at 2400 r / min for 60 min using a low-speed stirrer. The prepared positive electrode slurry was then uniformly coated onto an aluminum foil (positive electrode current collector) with a thickness of 14 μm and an areal density of 10 mg / cm³. 2 After drying (baking), rolling, slitting, and die-cutting, the positive electrode sheet is prepared. After coating, the electrode sheet is baked at 150℃ for 10 hours, and the maximum compaction density of the positive electrode sheet is 2.3 g / cm3.

[0068] Preparation of the negative electrode sheet: 93.6 wt% of hard carbon negative electrode material, 1.2 wt% of CMC binder, and 2 wt% of acetylene black conductive agent were mixed and stirred at 1200 rpm for 20 min using a low-speed mixer. The CMC binder was prepared from deionized water and CMC (carboxymethyl cellulose), with a CMC content of 1.2 wt%. Then, 40% solids content styrene-butadiene rubber latex binder (3.2 wt%) was added, and the mixture was stirred at 300 rpm for 1 hour. The prepared negative electrode slurry was then uniformly rolled onto a 14 μm thick aluminum foil (negative electrode current collector), with an areal density of 6.3 mg / cm³. 2 After drying (baking), slitting, and die-cutting, negative electrode sheets are prepared.

[0069] The obtained positive electrode, negative electrode, and 16μm thick polypropylene separator are stacked sequentially in the order of separator / negative electrode / separator / positive electrode, with 15 positive electrode sheets and 16 negative electrode sheets. The resulting sodium-ion core is sealed in an aluminum-plastic film to obtain a sodium-ion battery with a designed capacity of 2Ah.

[0070] The electrolyte consists of sodium hexafluorophosphate and a solvent. The concentration of sodium hexafluorophosphate is 1 mol / L, and the solvent is ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC) = 1:1:1 (mass ratio). The obtained sodium-ion full battery is baked in a high-temperature vacuum chamber for 24 hours. The electrolyte is injected at a rate of 5 g / cell. After electrolyte injection, the battery undergoes formation, aging, and capacity testing to prepare a lithium-ion battery. The battery undergoes a degassing process after formation and before aging.

[0071] Table 1

[0072] The coin cell capacity-voltage curves of Examples 1 and 2 and Comparative Example 1 are as follows: Figure 2 Cycle retention curve as shown Figure 3 ;Depend on Figure 2 , 3 As can be seen from the data comparison in Table 1, the present invention has a greater improvement in cycle performance than commercially available Prussian blue at a similar energy density, and a greater improvement in energy density than commercially available sodium iron phosphate pyrophosphate cathode material (Comparative Example 2), while maintaining comparable cycle performance.

[0073] The difference between Comparative Example 3 and Example 1 is that no surface modification was performed on the synthesized Prussian blue. Its specific capacity, energy density, and capacity retention were significantly lower than those of Example 1. This may be because a positively charged polymer was used to electrostatically adsorb the Prussian blue, making its surface positively charged, or a silane coupling agent was used to introduce functional groups such as amino groups. This can enhance the adsorption capacity of the Prussian blue surface for polyanionic precursor ions, promote the growth of a uniform and dense shell, and allow the polyanionic shell to play a good physical barrier and stabilize the interface, thereby improving the overall electrical performance, especially the cycle life.

[0074] In summary, the composite sodium-ion cathode material of this invention is prepared by first co-precipitating iron-based Prussian blue (FeHCF), followed by hydrothermal coating of a polyanion shell. The resulting core is surface-modified Prussian blue. This surface modification includes using a positively charged polymer to electrostatically adsorb and make the Prussian blue surface positively charged, or using a coupling agent to introduce functional groups such as amino groups, which can enhance the adsorption capacity of the Prussian blue surface for polyanion precursor ions and promote the growth of a uniform and dense shell. In the composite cathode material with "Prussian blue as the core and polyanion as the shell" provided by this invention, the core Prussian blue exerts its high capacity and excellent rate performance; the outer shell polyanion mainly acts as a physical barrier and stabilizes the interface. Utilizing the stable structure and excellent cycling performance of the polyanion material, a robust "protective shell" is provided for the entire particle, reducing structural damage during cycling and improving the overall cycle life.

[0075] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.